Search for Rare Copy-Number Variants in Congenital Heart Defects Identifies Novel Candidate Genes and a Potential Role for FOXC1 in Patients With Coarctation of the Aorta. (February 2016) - Sanchez-Castro, Marta; Eldjouzi, Hadja; Charpentier, Eric; Busson, Pierre-François; Hauet, Quentin; Lindenbaum, Pierre; Delasalle-Guyomarch, Béatrice; Baudry, Adrien; Pichon, Olivier; Pascal, Cécile; Lefort, Bruno; Bajolle, Fanny; et al.
Abstract : Background—: Congenital heart defects are the most frequent malformations among newborns and a frequent cause of morbidity and mortality. Although genetic variation contributes to congenital heart defects, their precise molecular bases remain unknown in the majority of patients. Methods and Results—: We analyzed, by high-resolution array comparative genomic hybridization, 316 children with sporadic, nonsyndromic congenital heart defects, including 76 coarctation of the aorta, 159 transposition of the great arteries, and 81 tetralogy of Fallot, as well as their unaffected parents. We identified by array comparative genomic hybridization, and validated by quantitative real-time polymerase chain reaction, 71 rare de novo (n=8) or inherited (n=63) copy-number variants (CNVs; 50 duplications and 21 deletions) in patients. We identified 113 candidate genes for congenital heart defects within these CNVs, including BTRC, CHRNB3, CSRP2BP, ERBB2, ERMARD, GLIS3, PLN, PTPRJ, RLN3, and TCTE3 . No de novo CNVs were identified in patients with transposition of the great arteries in contrast to coarctation of the aorta and tetralogy of Fallot ( P =0.002; Fisher exact test). A search for transcription factor binding sites showed that 93% of the rare CNVs identified in patients with coarctation of the aorta contained at least 1 gene with FOXC1-binding sites. This significant enrichment ( P <0.0001; permutation test) was not observed for the CNVs identified in patients with transposition of the great arteries and tetralogy of Fallot. We hypothesize that these CNVs may alter the expression of genes regulated by FOXC1. Foxc1 belongs to the forkhead transcription factors family, which plays a critical role in cardiovascular development in mice. Conclusions—: These data suggest that deregulation of FOXC1 or its downstream genes play a major role in the pathogenesis of coarctation of the aorta in humans. Abstract : Supplemental Digital Content is available in the text.